Perspective—Supercapacitor-Powered Flexible Wearable Strain Sensors. (1st March 2023) - Manjunatha, C.; Shwetha, K. P.; Athreya, Y.; Kumar, S. G.; Kamath, M. K. Sudha
Abstract : Currently and also in future, the flexible and wearable strain sensor would be in high demand due to its direct applications in biomedical health monitoring and other engineering applications. The challenge is to make the flexible and wearable sensor to function continuously with no additional wired powered supply system. In line with this, there has been considerable research works towards the integration of supercapacitor into flexible and wearable strain sensors, to make them self-powered and more efficient. This perspective provides more insights on design and fabrication of flexible and wearable strain sensor, working, components, and materials used, integration with supercapacitor, challenges and future scope.